SINTESIS TURUNAN HIDRAZON DARI VANILIN SEBAGAI SENSOR KOLORIMETRI ANION - , SUHARMAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Anion sensor based on hydrazone and azo-hydrazone derivatives from vanillin have been synthesized. The azo compound of 4-hydroxy-3-methoxy-5- (phenylazo)benzaldehyde was produced by diazotation reaction of vanillin (receptor 1). The azo-hydrazone compound 2-methoxy-6-(phenyldiazenyl)-4-(2- (2,4-dinitrophenyl)hydrazone)methyl)phenol (receptor 3) and 2-methoxy-6- (phenyldiazenyl)-4-(2-phenyhydrazone)methyl)phenol ( receptor 4) were synthesized by addition-elimination reaction of 4-hydroxy-3-methoxy-5-(phenylazo) benzaldehyde, while 4-((2-(2,4-dinitrophenyl)hydrazone)methyl)-2-methoxyphenol (receptor 2) was synthesized by addition-elimination reaction of vanillin and 2,4-dinitrophenylhydrazine. Synthesis of azo 4-hydroxy-3-methoxy-5-(phenylazo)benzaldehyde, receptor 2, 3 and 4 resulted in yield 72